Mobility and lifestyles of the romanian gypsy population. A case study in southern Spain - Montoya-Fernández, María Luna; Gutiérrez-Sánchez, José David (Acciones e Investigaciones Sociales, 2023)
Abstract This qualitative article focuses on the causal factors of the mobility of the Romanian Roma population to the province of Seville (Andalusia, Southern Spain) and their current lifestyle in environments located in the outskirts of cities. The research was carried out through an exploratory study in different territories (Ecija, Utrera, Los Palacios and Seville city). In addition, 35 interviews were conducted with men and women between 21 and 72 years born in Romania. The findings have made it possible, on the one hand, to get to know the Romanian Roma population living in stigmatised and socially vulnerable conditions on the outskirts of different cities, and on the other hand, the characteristics that accompany the mobility of the population in their journey to improve their living conditions. It concludes by highlighting the capacity for adaptation and mobility of the group under study in the face of complex situations of social exclusion. Furthermore, it stresses the need to intervene in order to provide lasting solutions from the Social Services, which should programme specific actions with this type of population living in exclusion and which has its own characteristics.